Air conditioning and refrigeration - North Caroline State University ([North Caroline] : North Caroline State University)
Teach yourself how to troubleshoot and repair air-conditioning equipment. These step-by-step instructions come with over 325 original graphics, full-color, interactive areas, animation, and voice-over
System requirements: Windows 95, 98, NT, XP ; 100 MHZ Pentium Processor ; 4x CD-ROM Drive ; 8 MB RAM
Keywords: Air conditioning; Refrigeration and refrigerating machinery